2015
DOI: 10.1134/s1063783415010205
|View full text |Cite
|
Sign up to set email alerts
|

Synergetics of the interaction of mobile and immobile dislocations in the formation of dislocation structures in a shock wave. Effect of the stacking fault energy

Abstract: A kinetic equation for the density of dislocations, which reflects the main stages of the formation of dislocation structures of different types in a shock wave, has been formulated based on the analysis of the interaction of two kinetic processes described by reaction-diffusion type equations for densities of mobile dislocations and dislocations forming immobile dipoles, respectively. It has been shown that an inhomoge neous (cellular) dislocation structure is formed at relatively low pressures behind the fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Cell walls differ from grain boundaries as they exhibit lower misorientation and a different morphology [50]. At low strain, these cell structures are rather heterogeneous, but as further deformation is introduced into the material, a much more uniform distribution of dislocations is observed [6,[47][48][49]. It has also been reported that in low stacking fault energy materials, the deformation process/formation of cell structure, is accompanied by the formation of deformation induced martensite, first as ε martensite and then as α' martensite [6,47].…”
Section: Effect Of Cw and Applied Stress Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell walls differ from grain boundaries as they exhibit lower misorientation and a different morphology [50]. At low strain, these cell structures are rather heterogeneous, but as further deformation is introduced into the material, a much more uniform distribution of dislocations is observed [6,[47][48][49]. It has also been reported that in low stacking fault energy materials, the deformation process/formation of cell structure, is accompanied by the formation of deformation induced martensite, first as ε martensite and then as α' martensite [6,47].…”
Section: Effect Of Cw and Applied Stress Levelsmentioning
confidence: 99%
“…The heterogeneous stress state is due to the plastic deformation process that materials with low stacking fault energy, such as ASS [46], undergo. As plastic deformation is introduced into ASS, the planar dislocation structure evolves into stacking faults [6,[47][48][49]. As more deformation is induced, the stacking faults form a cell structure.…”
Section: Effect Of Cw and Applied Stress Levelsmentioning
confidence: 99%